Glucagon-Like Peptide-1 Receptor Agonist Protects Against Diabetic Cardiomyopathy by Modulating microRNA-29b-3p/SLMAP - Fang P; Ye Z; Li R; She D; Zong G; Zhang L; Xue Y; Zhang K (Dove Medical Press, 2023)
Ping Fang,1 Zhengqin Ye,1 Ran Li,1 Dunmin She,2 Guannan Zong,1 Liya Zhang,1 Ying Xue,1 Keqin Zhang1 1Department of Endocrinology and Metabolism, Tongji Hospital, School of Medicine, Tongji University, Shanghai, 200065, People's Republic of China; 2Department of Endocrinology, Northern Jiangsu People's Hospital Affiliated to Yangzhou University, Yangzhou, Jiangsu, 225001, People's Republic of ChinaCorrespondence: Ying Xue; Keqin Zhang, Department of Endocrinology and Metabolism, Tongji Hospital, School of Medicine, Tongji University, No. 389, Xincun Road, Shanghai, 200065, People's Republic of China, Tel +86-21-66111061, Email doxy0622@163.com; 13621798084@126.comPurpose: Our aims were to investigate the pathogenesis of diabetic cardiomyopathy (DCM) and to explore the protective effect of glucagon-like peptide-1 receptor agonist (GLP-1RA) on DCM.Methods: After 12 weeks of treatment with exenatide-loaded microspheres, a long-acting GLP-1RA, in DCM mice, cardiac structure and function were evaluated by plasma B-type natriuretic peptide (BNP), echocardiography, H&E, oil red and Sirius staining. The expression of glucagon-like peptide-1 receptor in mouse heart tissue was determined by immunofluorescence staining. The label-free proteomic analysis of cardiac proteins was conducted among control, DCM and DM+GLP-1RA groups. Then, quantitative real-time PCR, Western blotting and dual-luciferase reporter assay were performed to verify the regulation of target protein by the upstream microRNA (miRNA).Results: GLP-1RA treatment obviously improved serum BNP, myocardial fibrosis, lipid deposition of the myocardium and echocardiography parameters in DCM mice. Sarcolemmal membrane-associated protein (SLMAP) was one of 61 differentially expressed cardiac proteins found in three groups by proteomic analysis. Up-regulation of microRNA-29b-3p (miR-29b-3p) and down-regulation of SLMAP were found in the ventricular myocardium of GLP-1RA-treated DCM mice. SLMAP was a target of miR-29b-3p, while GLP-1RA regulated SLMAP expression through miR-29b-3p. Furthermore, inhibition of glucagon-like peptide-1 receptor (GLP-1R) in cardiomyocytes reversed the effects of GLP-1RA on miR-29b/SLMAP.Conclusion: SLMAP may play roles in the pathogenesis of DCM and may be a target of GLP-1RA in protecting against DCM. After binding to myocardial GLP-1R, GLP-1RA can regulate the expression of myocardial SLMAP through miR-29b-3p.Keywords: diabetic cardiomyopathy, microRNA-29b-3p, proteomics, sarcolemmal membrane-associated protein, glucagon-like peptide-1 receptor agonist